Neoliberalismo e flexibilização do ensino médio no Brasil: a mercadorização da educação na Lei 13.415/2017 - Araújo Júnior, João Ferreira de (2020)
This work is taken under the research field called “Fundamentals of Educational Processes” as part of the Graduate Program at the Faculty of Education of the Federal University of Goiás. It aims at understanding the reform of the brazilian high school system which was legalized around 2016-2017. In this regard, it addresses bill 13.415, from February 17, 2017, based on its historical context, content and passing in the National Parliament. It identifies its explanatory bases on the principle of flexibility which cuts across the productive restructuring of contemporary capital and on neoliberalism. This is a documentary research. The guiding ideals and characteristics that bring the bill closer to neoliberal foundations were searched in the text and in the preambles of the legislation. The search was taken with an emphasis on both the privatization tendency of public high school and in it. It concludes that bill 13.415 / 2017 not only underlies the interests of the dominant class that led the 2016 coup d'état in Brazil but also promotes the commodification of high school, assuming an entrepreneurial subjectivity aligned with market freedom and neoliberal foundation.